Phase imperfect collaborative event driven energy efficient protocol. (21st November 2014) - Andelic, M.; Berber, S.; Swain, A.
The present paper proposes a novel Collaborative Event Driven Energy Efficient Protocol (CEDEEP) for single hop event driven Wireless Sensor Networks (WSN) with phase imperfect collaborative communication. CEDEEP takes advantages of spatiotemporal features of event driven WSN and uses collaborative communication to conserve more energy. In this research the effects of imperfectly phase synchronised signals on the performance of CEDEEP for collaborative event driven WSN have been investigated. An analytical model of the network is developed and the effectiveness of CEDEEP is considering in Rayleigh fading and Additive White Gaussian Noise (AWGN) channel. The results of the simulation confirmed CEDEEP efficiency even when imperfect phase synchronisation exists between received collaborative signals. Therefore, this research gives strong evidences of CEDEEP ability to ensure high energy efficient operation of phase imperfect collaborative event driven WSN over Rayleigh fading and AWGN channels.